Antipsychotic profile of cannabidiol - Pedrazzi, João Francisco Cordeiro; Pereira, Ana Carolina de Castro Issy; Gomes, Felipe Villela; Del Bel, Elaine (Medicina (Ribeirao Preto), 2014)
Cannabidiol an important phytocannabinoid present in the Cannabis sativa opposing to the major plant compound D9-tetrahydrocannabinol, known as delta-9-THC, is devoid of the psychotomimetic effects. Growing set of evidence suggest that cannabidiol may be used for the treatment of the symptoms of psychiatric disorders such as depression, anxiety and psychosis. The first evidence of the cannabidiol therapeutic potential was the observation of its ability to antagonize delta-9-THC effects either on human and experimental animal models. Pharmacological effects of CBD has been investigated in different biological systems, in vitro and in vivo, however, the mechanisms responsible for their therapeutic potential are still unclear. delta-9-THC effects results from activation of the cannabinoid receptors CB1 and CB2, however, the cannabidiol has low affinity for these receptors. The good tolerability of canabidiol in human trials makes this compound an interesting target of the scientific community. The aim of this paper is to present concisely some experimental and clinical evidence about the cannabidiol antipsychotic profile.